(untitled) (Gestionar: revista de empresa y gobierno, 2022)
The main objective was oriented to study the management of public policies in education in the municipal, national, and international contexts in Venezuela. The methodology applied was bibliographic research, which allowed an exhaustive exploration of studies and research and authors who have investigated the formative processes and directional strategies for a harmonious development of this fundamental service to the community. Among the results, the main limitation of the government’s educational public policies is the bureaucracy in realizing plans and projects, in the sense of possible restrictions when designing, executing, and establishing a service that responds to social demands. In conclusion, the type of policies is applied according to the objectives and aspirations of the government and the kind of citizen to be educated, which implies using and executing actions that tend to improve institutional conditions, teacher preparation, and curricular revision. For this reason, it is recommended to continue delving into the subject of political management and governmental actions on an ongoing basis.